DEPLOYMENT OF ERTMS IN CZECH REPUBLIC - Jiří Vopava; Mária Jánešová; Radek Kratochvíl (Acta Polytechnica CTU Proceedings)
The article describes current situation and expected deployment of international standard for automatic rail vehicle protection in Czech Republic for period 2014 – 2020. Article introduces expected status in 2020 and subsequent implementation of commitments until 2026. It introduces expected result of gradual implementation for tracks and vehicles. It also displays brief deployment overview of European Rail Traffic Management System in European Union countries for each level of European Train Control System.